Somatostatin analogs in the treatment of neuroendocrine tumors: current and emerging aspects. (2nd November 2017) - Mazziotti, Gherardo; Mosca, Alessandra; Frara, Stefano; Vitale, Giovanni; Giustina, Andrea
ABSTRACT: Introduction : Neuroendocrine tumors (NETs) harbor somatostatin receptors and there is a strong rationale for using somatostatin analogs (SSAs) for treatment of NETs. Areas covered : This article discusses i) pharmacology of somatostatin and its analogs; ii) antisecretory and anti-proliferative effects of SSAs in NETs; iii) efficacy and safety of emerging therapeutic regimens with first generation SSAs administered at either high doses or in combination with antineoplastic drugs; iv) efficacy and safety of pasireotide and chimeric molecules; v) efficacy of radionuclide therapy of NETs using SSAs. Expert opinion : SSAs are the first-line medical therapy for functioning and non-functioning well-differentiated NETs. In patients not responder to first generation SSAs, the increase of drug dose over the conventional regimens, the combination of SSAs with other biotherapies or molecular targeted therapies, the switch to pasireotide or the use of SSAs in radionuclide therapy may improve the therapeutic success.